THE INTERMEDIATING ROLE OF FINANCIAL LITERACY IN THE MICROFINANCE SUSTAINABILITY NEXUS: EVIDENCE FROM WOMEN-LED SMES IN NIGERIA - Agbeyinka Yinka Ibrahim (Gusau Journal of Accounting and Finance)
This study examines the interconnected roles of microfinance access and financial literacy in enhancing business sustainability among women-led small and medium enterprises (SMEs) in Nigeria. Drawing on cross-sectional survey data from 3,421 women entrepreneurs across urban and peri-urban regions, the study employs a mediation analysis within an Ordinary Least Squares (OLS) framework, supported by bootstrapping procedures and robustness checks using structural equation modelling. The empirical findings reveal that access to microfinance significantly enhances business sustainability, while financial literacy independently contributes to sustainability outcomes. Importantly, financial literacy mediates the relationship between microfinance and business sustainability, with a statistically significant indirect effect, validated by the Sobel test and bootstrapped confidence intervals. Control variables such as age, education, and business location further contextualize the findings. These results highlight the critical role of cognitive and educational capabilities in translating access to finance into sustainable business performance. Policymakers and development practitioners are encouraged to embed financial literacy training within microfinance schemes and develop targeted programs for rural and underserved populations. Future research should adopt longitudinal and experimental designs to validate causality and assess sectoral and digital moderating factors in the financial empowerment of women entrepreneurs.